Responses of Soil Enzymes and Carbon Mineralization to Applied Organic Amendments: A Short-term Study in Acidic Sandy Loam Soil - Nirmali Gogoi and Rupam Kataki, Banashree Sarma, Bikram Borkotoki (Journal of the Indian Society of Soil Science, 2017)
Predicting carbon (C) mineralization due to fertilizer application is important for predicting carbon dioxide (CO2) emissions into the atmosphere. This study was conducted to evaluate the effects of different organic amendments and inorganic fertilizers on C mineralization and soil enzyme activities along with the changes in soil pH, available nitrogen (N) and phosphorus (P). Eight treatments were applied using inorganic fertilizer and organic amendments (FYM, vermicompost and biochar) at different rates. Higher activities of soil enzymes (urease, phosphatase and dehydrogenase) were recorded till 60 days of incubation with addition of organic amendments. Among the applied organic amendments, vermicompost showed greater availability of N and P. Both vermicompost and FYM application recorded enhanced activities of soil enzymes and C mineralization rate while biochar application noted higher C half-life and soil pH. Thus, addition of biochar in acid soil would be a sustainable option to reduce the C mineralization which also maintains nutrient status of sandy loam soil of north-east India.